If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -5 = 6x + -13 Reorder the terms: -5 + 4x = 6x + -13 Reorder the terms: -5 + 4x = -13 + 6x Solving -5 + 4x = -13 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -5 + 4x + -6x = -13 + 6x + -6x Combine like terms: 4x + -6x = -2x -5 + -2x = -13 + 6x + -6x Combine like terms: 6x + -6x = 0 -5 + -2x = -13 + 0 -5 + -2x = -13 Add '5' to each side of the equation. -5 + 5 + -2x = -13 + 5 Combine like terms: -5 + 5 = 0 0 + -2x = -13 + 5 -2x = -13 + 5 Combine like terms: -13 + 5 = -8 -2x = -8 Divide each side by '-2'. x = 4 Simplifying x = 4
| 5-(x+3)+3x+3(x+2)= | | -18+12-3= | | (9x+9)+(-12x+24)= | | 4(x+3)+(x+6)+2(x-3)= | | 160s+465(88-s)=19265 | | n^2+14n-95=0 | | 0=7x-28 | | (x-5i)(x+5i)=0 | | 2x+y-3x+4y-6+5y= | | 1/3(2x+9)=2/3x+3 | | 5x+20=15+10x | | a-16=2(3-a) | | 9y=18x-54 | | 2p+9-8p=3p-18 | | 3(x+2)=2(x+1)-5 | | 8y-6=4y-18 | | 3a+22=7a+14 | | 2n-8=6n-32 | | 2(2x+6)=5x+9 | | 16x+27=75 | | -18=6k+6(1+3k) | | 2n-8=6n-(-32) | | f-14=6f | | 4(x+3)-12=3(x-6) | | 4x^3-12x^2-64x+192=0 | | -12=5v+2+2v | | -3b+2b-3b=6 | | 7h-18=31 | | 3x-11=-14 | | -6Y+4(Y-7)=-18 | | -20-8n=-4(n+8) | | 10x+6(300-x)=2000 |